2017
DOI: 10.1177/1010428317721620
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of cell cycle progression in BRAFV600E inhibitor–resistant human melanoma by a chromatin modifier

Abstract: The BRAF V600E -specific inhibitor vemurafenib blocks mitogen-activated protein kinase pathway and induces cell cycle arrest at G0/G1 phase leading to apoptosis of melanomas. To gain an understanding of the dynamics of cell cycle regulation during vemurafenib therapy, we analyzed several vemurafenib-resistant human melanoma sublines derived from BRAF V600E harboring vemurafenib-sensitive parental lines. Vemurafenib provoked G0/G1 phase arrest in parental but not in vemurafenib-resistant sublines. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Based on our findings, BRAF V600E inhibition blocks CDC7-downstream MCM2 and ERK1/2 activities in parental, but not in resistant cells. This was supported by the evidence that Vemurafenib treatment provoked cell cycle arrest associated with cytostatic and cytotoxic effects in parental, but not in resistant cells 38,39 . To further examine whether CDC7 inhibition could sensitize resistant melanoma cells to Vemurafenib, a pharmacologic selective CDC7 inhibitor, TAK-931, was used to manipulate the kinase activity.…”
Section: Discussionmentioning
confidence: 75%
“…Based on our findings, BRAF V600E inhibition blocks CDC7-downstream MCM2 and ERK1/2 activities in parental, but not in resistant cells. This was supported by the evidence that Vemurafenib treatment provoked cell cycle arrest associated with cytostatic and cytotoxic effects in parental, but not in resistant cells 38,39 . To further examine whether CDC7 inhibition could sensitize resistant melanoma cells to Vemurafenib, a pharmacologic selective CDC7 inhibitor, TAK-931, was used to manipulate the kinase activity.…”
Section: Discussionmentioning
confidence: 75%
“…The BRAF-V600E mutation is present in approximately 50% of melanoma cases and causes constitutive activation of BRAF and the MAPK (ERK) signaling pathway leading to uncontrolled cell proliferation ( Ascierto et al 2012 ). Vemurafenib binds specifically to the adenosine triphosphate (ATP) binding pocket of activated BRAF-V600E, blocks ERK1/2 activation, and induces cell cycle arrest and apoptosis ( Torres-Collado et al 2017 ). Although there is short-term tumor regression and enhancement of patient survival, resistance to vemurafenib frequently develops ( Ascierto et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that treatment of SK-MEL-19 and SK-MEL-27 melanoma cells with prodiginine induced G1/G0 phase arrest and cell apoptosis via downregulating survivin [35]. Furthermore, the BRAF V600E -specific inhibitor, vemurafenib, could inhibit the MAPK pathway, which in turn promoted cell cycle arrest at the G0/G1 phase of the cell cycle, eventually leading to melanoma cell apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%